2015
DOI: 10.1017/s0031182015000013
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity, not genetic variation, drives infection success of a fungal parasite

Abstract: Hosts strongly influence parasite fitness. However, it is challenging to disentangle host effects on genetic vs plasticity-driven traits of parasites, since parasites can evolve quickly. It remains especially difficult to determine the causes and magnitude of parasite plasticity. In successive generations, parasites may respond plastically to better infect their current type of host, or hosts may produce generally 'good' or 'bad' quality parasites. Here, we characterized parasite plasticity by taking advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 66 publications
1
49
0
2
Order By: Relevance
“…Metschnikowia bicuspidata traits can respond plastically to different host environments (Searle et al. ), but there is no variation in infectivity or virulence among isolates collected from different lakes (Duffy and Sivars‐Becker ; Searle et al. ).…”
Section: The Spatial Scale Of Host–parasite Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metschnikowia bicuspidata traits can respond plastically to different host environments (Searle et al. ), but there is no variation in infectivity or virulence among isolates collected from different lakes (Duffy and Sivars‐Becker ; Searle et al. ).…”
Section: The Spatial Scale Of Host–parasite Interactionsmentioning
confidence: 99%
“…), but there is no variation in infectivity or virulence among isolates collected from different lakes (Duffy and Sivars‐Becker ; Searle et al. ). The parasite also has not responded to selection in laboratory experiments (Duffy and Sivars‐Becker ; Auld et al.…”
Section: The Spatial Scale Of Host–parasite Interactionsmentioning
confidence: 99%
“…Recent studies have found essentially no genetic variation in the fungal pathogen, reducing the likelihood of genotype × genotype interactions (Searle et al. ). However, genetic variation within natural D. dentifera populations could influence pathogen transmission dynamics through heterogeneity in resistance, or spore production per host (Carius et al.…”
Section: Methodsmentioning
confidence: 99%
“…We have cultured this parasite on a variety of D. pulex genotypes since 2011 (and on genotypes of the host congener Daphnia dentifera since 2003, Hall et al ). In host D. dentifera, M. bicuspidata exhibits no detectable genetic variation across its range (Duffy and Sivars‐Becker , Searle et al ). This lack of parasite diversity, the corresponding absence of any significant response to selection (Auld et al ), and our use of novel D. pulex genotypes likely precluded the development of particular host genotype/parasite strain associations in our experiment.…”
Section: Methodsmentioning
confidence: 99%